Analysis of a cross groove constant velocity joint mechanism designed for high performance racing conditions. (March 2023) - Simpson, Matthew; Dolatabadi, Nader; Morris, Nick; Rahmani, Ramin; Jones, David; Craig, Christopher
Constant Velocity Joint (CVJ) mechanisms enable torque transmission between two shafts at a fixed or variable angle. Cross groove CVJs are typically used in high performance automotive applications due to their versatility and light weight. Critical failure modes, such as pitting or abrasive wear, occur due to the harsh tribological conditions at ball reversals. In this research, an existing mathematical model is developed further for the case of cross groove CVJs including an accurate contact mechanics model. The developed model is validated against a published data set from literature. Surface topography of worn raceways are experimentally measured and the results from the developed model are corroborated with the measured surface parameters. This improved model shows the correlations between predicted contact force variation and wear scar depths during ball reversals, hitherto not reported in the literature.